Barriers And Assessment Of Readiness Towards Mitigation To Constructability Implementation In Malaysia - Hasan, Riadh G. (2007)
Constructability is one of the new directions in the field of construction management. The application of constructability concepts in developed countries such as USA, UK and Australia has been proven to yield tangible benefits to the construction project stakeholders and in turn has leveraged the improvement of the construction industry in these countries. The Construction Industry Institute (CII) in USA stated that there are barriers that impede the implementation of constructability and designated the identification of these barriers as one of the steps in the first milestone of constructability implementation roadmap. Recent researches in constructability conducted in Malaysia showed that this concept is not yet adopted by the Malaysian construction industry. The lack of implementation of constructability by the construction project’s stakeholders in Malaysia indicates that there are barriers that oppose its adoption. Consequently the this research aimed at identifying those barriers together with their causes and studying the existence of the barriers among the main construction project stakeholders in addition to the readiness of the stakeholders to overcome the barriers. Based on the available literature twenty six potential barriers were formulated forming the basis for the broad questionnaire type survey research that was carried out to study the barriers to constructability implementation in Malaysia. The survey research was augmented by four case studies that were chosen to cover construction projects of different types and sizes. The cases also served as means of identifying the main causes behind the existence of the major barriers. The research findings showed that fifteen out of the twenty six barriers were major barriers that were claimed to exist by more than fifty percent of the respondents. The highest ranking barrier in the study was the absence of systematic documentation and retrieval of “lesson learned”. Furthermore, the three main categories of the construction project organization types were found to have nearly equal number of barriers with designers and the contractors’ organizations having slightly higher number of existed barriers than the owners. The designers and contractors had sixteen barriers compared with fourteen in the owners’ organizations.Finally, this research concluded that the Malaysian main project stakeholders have an understanding of the need to remove severe barriers. And as an indication of the high readiness of the Malaysian construction industry to mitigate the barriers, the research showed that the probability of high readiness of the construction project stakeholders to overcome the barriers was more than 50 percent for 11 out of the 15 major barriers.